Phase- and intensity-resolved measurements of above threshold ionization by few-cycle pulses. (11th June 2018) - Kübel, M; Arbeiter, M; Burger, C; Kling, Nora G; Pischke, T; Moshammer, R; Fennel, T; Kling, M F; Bergues, B
Abstract: We investigate the carrier-envelope phase (CEP) and intensity dependence of the longitudinal momentum distribution of photoelectrons resulting from above threshold ionization of argon by few-cycle laser pulses. The intensity of the pulses with a center wavelength of 750 nm is varied in a range between 0.7 × 10 14 and 5.5 × 10 14 W cm − 2 . Our measurements reveal a prominent maximum in the CEP-dependent asymmetry at photoelectron energies of 2 U P ( U P being the ponderomotive potential), that is persistent over the entire intensity range. Further local maxima are observed around 0.3 and 0.8 U P . The experimental results are in good agreement with theoretical results obtained by solving the three-dimensional time-dependent Schrödinger equation. We show that for few-cycle pulses, the amplitude of the CEP-dependent asymmetry provides a reliable measure for the peak intensity on target. Moreover, the measured asymmetry amplitude exhibits an intensity-dependent interference structure at low photoelectron energy, which could be used to benchmark model potentials for complex atoms.